Comparison of labour requirements for cropping maize on land previously used for stylosanthes fodder banks and on adjacent fallows in the sub-humid zone of Nigeria - Tarawali, G.; Mohamed-Saleem, M.A.; Kaufmann, Ralph R. von (1987)
Examines the returns to labour from cropping fallowed land and land that has been used for stylosanthes fodder banks in the subhumid zone of Nigeria.